2013
DOI: 10.1002/sia.5219
|View full text |Cite
|
Sign up to set email alerts
|

Anodizing of AA6063 aluminium alloy profiles: Generation of dark appearance

Abstract: The generation of dark appearance on an anodized AA6063-T6 aluminium alloy profile has been investigated. Plan and cross-sectional views of the anodic films of normal and dark samples revealed a distinct layer, of 1-2 mm thickness, decorated with characteristic features in the outer film regions of the dark sample, contrasting with typical porous anodic film of the normal sample. Additionally, it was revealed that the alloy substrate of the dark sample was over-aged and the characteristic features in the outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Certainly, the KHR model represents a perfect idea of the layer design but can actually be observed, as impressively shown in Figure 5, [36] which is an example of an oxide layer formed on technical pure aluminum in sulfuric acid, but also as low alloyed aluminum alloys. [37][38][39][40] Incidentally, the fracture pattern reveals the intercellular break, typically for anodic films with small pore sizes as formed in sulfuric acid anodizing F I G U R E 2 TEM image of anodic oxide film formed during anodizing according to an experiment as shown in Figure 1. [24] TEM, transmission electron microscopy.…”
Section: Nanopores-conventional Anodizing Layersmentioning
confidence: 99%
“…Certainly, the KHR model represents a perfect idea of the layer design but can actually be observed, as impressively shown in Figure 5, [36] which is an example of an oxide layer formed on technical pure aluminum in sulfuric acid, but also as low alloyed aluminum alloys. [37][38][39][40] Incidentally, the fracture pattern reveals the intercellular break, typically for anodic films with small pore sizes as formed in sulfuric acid anodizing F I G U R E 2 TEM image of anodic oxide film formed during anodizing according to an experiment as shown in Figure 1. [24] TEM, transmission electron microscopy.…”
Section: Nanopores-conventional Anodizing Layersmentioning
confidence: 99%
“…However, with recent increase in the use of recycled Aluminium alloys for environmental sustainability and cost effectiveness, the quality control of anodised surfaces is increasingly becoming difficult. This is due to the higher degree of heterogeneity in recycled Al alloys that contain a higher number of intermetallic or constituent phase particles, which leads to higher heterogeneity in the electrochemical nature thus altering the anodising behaviour and the decorative finish of the anodised surface [9,[49][50][51][52][53][54][55][56][57]. Various authors have emphasized on the importance of the alloy composition, morphology and microstructure of the Al surface and its effect on the anodising behaviour and optical appearance [58] [59].…”
Section: Introductionmentioning
confidence: 99%
“…The grain orientation could affect the gas generation, which may influence the extent of roughening of the anodizing film during the anodizing process . Zhou found that the over‐aged microstructure and abnormal anodizing conditions at the commencement of anodizing process can result in the dark anodizing film . L.E.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Zhou found that the over-aged microstructure and abnormal anodizing conditions at the commencement of anodizing process can result in the dark anodizing film. [17] L.E. Fratila-Apachitei investigated the anodizing process for three different aluminum alloys, i.e.…”
Section: Introductionmentioning
confidence: 99%